Successful Entrepreneurs Come From the Top of the Earned Income Distribution - Niklas Garnadt; Lena Füner; Konrad Stahl; Joacim Tag (CESifo GmbH, 2025)
Identifying high growth startups ex-ante and fostering their success is an important policy challenge. Using Swedish registry data, we show that previous labor market earnings of entrepreneurs is a simple observable that is strongly correlated with entrepreneurship success. Entrepreneurs from the top decile of income from dependent employment are four times more likely to succeed than those from the lowest decile. Their firms are larger and more productive from the outset, and this effect intensifies over time. This correlation is virtually unaffected by variations in the entrepreneurs' personal traits. It does also not vary across the business cycle.
Keywords: L26; J24; M13; 330; entrepreneurship; high-growth startups; labor income; unemployment